2022
DOI: 10.3389/fmars.2022.907065
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Interacting Proteins of Transcription Factor DpAP2 Related to Carotenoid Biosynthesis From Marine Microalga Dunaliella parva

Abstract: Carotenoids are widely distributed and structurally diverse, which have significant roles in the photosynthesis of plants. As a precursor of vitamin A, carotenoids are also antioxidants that reduce various chronic diseases, which are beneficial for human health. Currently, the existing studies concerned the biological roles of APETALA2 (AP2)/ethylene-responsive factor (ERF) genes originated from higher plants. The AP2 superfamily of the transcriptional regulator was identified in higher plants, which was relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Specifically, DpAP2 can interact with three proteins, which may be associated with multiple biological processes. This lays a good foundation for a deep understanding of the regulatory mechanisms of DpAP2 and genetic engineering breeding (Shang et al, 2022). Recently, a comprehensive survey of genes and enzymes related to the carotenoid biosynthetic pathway has now been conducted, and structural modeling of three important enzymes, 1-deoxy-D-xylulose 5-phosphate reductase (DXR), 15-cis-phytoene synthase (PSY), and zeta-carotene desaturase (ZDS), has been achieved (Narang et al, 2021).…”
Section: Carotenoidsmentioning
confidence: 94%
“…Specifically, DpAP2 can interact with three proteins, which may be associated with multiple biological processes. This lays a good foundation for a deep understanding of the regulatory mechanisms of DpAP2 and genetic engineering breeding (Shang et al, 2022). Recently, a comprehensive survey of genes and enzymes related to the carotenoid biosynthetic pathway has now been conducted, and structural modeling of three important enzymes, 1-deoxy-D-xylulose 5-phosphate reductase (DXR), 15-cis-phytoene synthase (PSY), and zeta-carotene desaturase (ZDS), has been achieved (Narang et al, 2021).…”
Section: Carotenoidsmentioning
confidence: 94%
“…For algae, overexpression of DpAP2 genes in Dunaliella parva could lead to an increase of carotenoid content; however, the regulatory mechanism of AP2/ERF transcription factors regulating carotenoid metabolism is unclear in algae.…”
Section: Regulation Of Carotenoid Biosynthesis By Regulators In Plant...mentioning
confidence: 99%
“…77 MaEIL9 positively regulated transcription of MaDXR1, MaPDS1, MaZDS1, and MaSPL16 through directly targeting their promoters, thus elevating carotenoid accumulation of banana fruit. 78 For algae, overexpression of DpAP2 genes in Dunaliella parva could lead to an increase of carotenoid content; 79 however, the regulatory mechanism of AP2/ERF transcription factors regulating carotenoid metabolism is unclear in algae.…”
Section: Regulation Of Carotenoid Biosynthesis By Regulators In Plant...mentioning
confidence: 99%
“…parva FACHB-815 was purchased from Freshwater Algae Culture Collection at the Institute of Hydrobiology (Wuhan, China). Cells of D. parva were cultured in Dm medium described by our previous study [6,22]. D. parva was cultured under light intensity of 34 μmol photons/ (m 2 xs) with day-night cycle (14 h light and 10 h dark) at 25˚C.…”
Section: Microalga and Growth Conditionmentioning
confidence: 99%
“…It was found that carotenoids content reached the highest values of 3.11mg/g DW and 2.78mg/g DW under the treatment of 40 ppm CaCl 2 and 80 ppm PEG, which increased by 58.67% and 41.84% compared with control group (1.96mg/g DW). Carotenoids are synthesized from several steps such as desaturation, cyclization, hydroxylation and epoxidation within the plastids [22]. Key enzymes of carotenoids synthesis pathway include DXS, DXR, GGPS, PSY and PDS.…”
Section: Plos Onementioning
confidence: 99%